PENGARUH KEPUASAN KERJA KARYAWAN TERHADAP KOMITMEN ORGANISASIONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) PADA PT. MAHARANI PREMA SAKTI DENPASAR - Devi, Dewa Ayu Windu Sari; Adnyani, I Gusti Ayu Dewi (E-Jurnal Manajemen; Vol 4 No 12 (2015), 2015)
This study aims to determine the effect of employee job satisfaction and organizational commitment organizational citizenship behavior ( OCB ) at PT. Maharani Prema Sakti Denpasar . This study uses path analysis , data quality test and classical assumption with causal research type of research that aims to prove a causal relationship of the variables studied . Based on path analysis can be concluded that job satisfaction is positive and significant effect on organizational commitment and organizational citizenship behavior (OCB) employees of PT . Maharani Prema Sakti Denpasar . This means that with an increase in employee satisfaction will increase significantly and affect the organizational commitment and organizational citizenship behavior of employees of PT . Maharani Prema Sakti Denpasar
Keywords: kepuasan kerja karyawan; komitmen organisasional; Organizational Citizenship Behaviour (OCB)